"When you are here, you have high blood pressure": Liberian refugees' health and access to healthcare in Staten Island, NY. Issue 1 (7th March 2016) - Ludwig, Bernadette; Reed, Holly
Abstract : Purpose: – The purpose of this paper is to examine health issues among Liberian refugees living in Staten Island and access potential barriers to accessing healthcare. Design/methodology/approach: – Qualitative methods including interviews ( n =68) with West African immigrants, predominantly Liberian refugees, and long-term ethnography were employed to elicit West Africans' views on health, acculturation, and access to service providers. Framework analysis was employed to analyze the data thematically. Findings: – Chronic health diseases, depression, isolation, and inadequate access to healthcare were the main concerns of the population studied. The findings are in contrast to the public health experts' concentration on infectious diseases. Practical implications: – The barriers to access proper healthcare have implications for healthcare providers and government institutions and information about these barriers can help them to refocus their health efforts to better address the needs of West African refugees. Originality/value: – Africans are among the newest immigrants in the USA and are considerably understudied compared to other groups such as Latin Americans and Asians. Additionally, there is an abundance research about refugees' health status when they first arrive in the USA, but there is little data on their health after their resettlement.